2017
DOI: 10.1111/nyas.13377
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation of phytochemicals in food and control: a review

Abstract: Phytochemicals are widely present in food and have been confirmed to be bioactive, thereby contributing to human health. However, some phytochemicals are sensitive to light owing to their structures and may suffer from photodegradation, especially when sensitizers exist, resulting in sensory quality change, nutrient loss in food, and even the formation of toxic compounds. The photooxidation of phytochemicals occurs through three different mechanisms: (1) by directly absorbing luminous energy, (2) with triplet-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The efficiency of each reaction type mainly depends on the relative concentrations of oxygen and substrate. Given that oxygen is more soluble in nonpolar lipids than in water, the formation of COPs in soybean oil containing chlorophyll mainly depends on the type II reaction, while the photo‐oxidation of cholesterol in water‐based foods such as milk mainly depends on Type I reaction (Lu & Zhao, 2017; Min & Boff, 2002). Generally speaking, the formation of COPs under light exposure depends largely on the exposure time and light energy.…”
Section: Generations Of Dietary Cholesterol Oxidation Products (Cops) During Food Processing and Storagementioning
confidence: 99%
“…The efficiency of each reaction type mainly depends on the relative concentrations of oxygen and substrate. Given that oxygen is more soluble in nonpolar lipids than in water, the formation of COPs in soybean oil containing chlorophyll mainly depends on the type II reaction, while the photo‐oxidation of cholesterol in water‐based foods such as milk mainly depends on Type I reaction (Lu & Zhao, 2017; Min & Boff, 2002). Generally speaking, the formation of COPs under light exposure depends largely on the exposure time and light energy.…”
Section: Generations Of Dietary Cholesterol Oxidation Products (Cops) During Food Processing and Storagementioning
confidence: 99%
“…However, a myriad of research studies on phytosterol have inevitably proved that intake of phytosterol has potential health benefits, hence it is suggested that phytosterols-rich foods such as seaweed can be used as functional foods [ 159 ]. Phytosterols are sensitive to oxidation-like cholesterol, resulting in the formation of phytosterol oxidation products by enzymatic or non-enzymatic mechanisms during heat processing, storage, and human metabolism [ 160 , 161 ]. Despite the low concentration of cholesterol oxidation products in food, they have been demonstrated to cause cytotoxicity and genotoxicity.…”
Section: Safety Of Phytosterolsmentioning
confidence: 99%
“…Analytical methods for the qualitative and quantitative analysis of phytosterols and cholesterol oxidation products (COPs) are prevalent [32][33][34][35][36] and may serve as a starting Figure 2. Auto-oxidation and photo-oxidation of phytosterols forming various polar and non-polar phytosterol oxidation products (POPs) [17,18].…”
Section: Analysis Of Phytosterol Oxidation Productsmentioning
confidence: 99%
“…Similar to cholesterol oxidation products, POPs are generated by auto-oxidation and photo-oxidation mechanisms ( Figure 2) [17,18]. Primarily, POPs are formed by the oxidation of the steroid ring of phytosterol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation